(untitled) (Eurasian Journal of Philology Science and Education, 2025)
The article examines the model of the national school and its basic principles proposed by Alma Kyraubayeva, a scientist and teacher, Doctor of Philology, whose goal is to improve the quality of the educational system. The author’s program of the teacher, methods and results of its implementation are considered on the basis of the Senim program. The system of work, the innovative specifics of the Humanitarian School-Lyceum of Kazakh culture, which has been tested in the educational process, involves the study of best practices in education, the effective use of advanced models. Alma Kyraubayeva emphasizes the specifics of the national school in accordance with the content of education, achievements in the educational process, effective acquisition of knowledge by students in the unity of diligence, will and activity from a psychological point of view. The Kazakh National School, presented by the scientist-teacher Alma Mutalipkyzy, is full of new ideas, methodological and didactic principles. The Kazakh National School is designed to raise issues of educating a generation capable of absorbing historical changes, national values, national language and national identity in order to form a Kazakh mentality, form a representative of an intellectual nation with a rich spiritual essence. The scientist is a teacher, justifying the ways of development of the national school in the pedagogical process, emphasizing the tasks and importance of innovative technologies. Keywords: national school, “Senim” program, national school model, author’s program, Kazakh phenomenon.